Seafarer Market – Challenges for the Future - Lušić, Zvonimir; Bakota, Mario; Čorić, Mirko; Skoko, Ivica (Transactions on Maritime Science, 2019)
In the today’s seafarer market one of the key problems is the lack of seafarers, especially experienced officers. Although the global supply of officers is increasing steadily, the demand is still above supply. An additional problem is that an increased demand may lead to a decreased quality of education. Ships and shipping technology in general have become more advanced and require well educated and trained personnel. In addition, over the next several decades it is expected that partial or fully autonomous vessels will be in commercial use, and this will require significant changes in the education and training of crew members. So, regarding the education of seafarers, the main future challenges include the ways of ensuring sufficient supply of seafarers, especially well-trained officers, and adapting the education systems for the upcoming introduction of autonomous ships. This paper analyzes the present situation of the seafarers and shipping market, and provides forecast for the near future. Also, the main challenges in education and training of seafarers will refer to observing the recommendations for improvement and adaptation to future demands.